SCONCERNING THE ISSUE OF GENERATIVE ART CLASSIFICATION: DEFINITION OF CONCEPTS / К ПРОБЛЕМЕ КЛАССИФИКАЦИИ GENERATIVE ART: РАЗРАБОТКА ПОНЯТИЙНОГО АППАРАТА - LUKICHEV RUSLAN V. / ЛУКИЧЕВ Р.В. (Наука телевидения)
The article refers to the problem of generative art taxonomy as a complex interdisciplinary phenomenon and analysis of its key features. The generative art is a relevant cultural and artistic phenomenon in Russian and foreign art that emerged in the 1910s within Russian and West European avant-garde painters and received a new boost for development thanks to contemporary computer technologies. Based on the classification model proposed by foreign researchers, M. Boden and E. Edmonds, the author of this article identifies concepts like Generative Art (G-art), Computer Art (C-art), Interactive Art (I-art), Interactive Computer Art (CI-art), and Computer Generative Art (CG-art) and introduces new scientific terms: Interactive Generative Art and Interactive Computer-Generated Art. The first one refers to a series of works of art created with the active participation of the audience and the use of traditional (noncomputer) autonomous systems that provide a certain degree of randomness without the implementation of multimedia technologies. The second one refers to a series of artworks created by autonomous computer systems and involving active interaction with the audience. These phenomena are considered based on the art object’s possessing the features of generative (G), interactive (I) or computer (C) vectors that underlie the classification method of Gen Art and adjacent contextual phenomena developed by the author and visually modeled by him in the Cartesian coordinate system. Emphasis was made on Interactive Computer-Generated Art. A media installation by Stain art group called Mobile Interactive Multi-Parametric Image (MIMPI) is provided as an example; it is an interactive audio-visual environment first introduced in MEL Space gallery (Moscow) in May 2012. Finally, the author comes to the conclusion that granting the generative art the status of a natural transitional phase in the art history of the 20th — early 21st centuries, as proposed by him, is justified, since this art combines “dry” and “wet” technologies and the corresponding types of cultures.